2004
DOI: 10.1007/s00210-003-0860-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparative pharmacology of human �-adrenergic receptor subtypes?characterization of stably transfected receptors in CHO cells

Abstract: Although many beta1-receptor antagonists and beta2-receptor agonists have been used in pharmacotherapy for many years their pharmacological properties at all three known subtypes of beta-adrenergic receptors are not always well characterized. The aim of this study was, therefore, to provide comparative binding characteristics of agonists (epinephrine, norepinephrine, isoproterenol, fenoterol, salbutamol, salmeterol, terbutalin, formoterol, broxaterol) and antagonists (propranolol, alprenolol, atenolol, metopro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

36
255
2
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 304 publications
(294 citation statements)
references
References 0 publications
36
255
2
1
Order By: Relevance
“…For example, the prototypical antagonist propranolol was reported to have K i values at β 1 -, β 2 ,-and β 3 -adrenoceptors of 1.8, 0.8, and 186 nM, respectively (Table 2). Similarly, much lower β 3 -than β 1 -and β 2 -adrenoceptor affinity was also reported for the clinically used drugs sotalol, alprenolol, carvedilol, metoprolol, atenolol, and bisoprolol in most studies (Baker 2005;Hoffmann et al 2004), although one study reported high β 3 -adrenoceptor affinity of carvedilol (Candelore et al 1999). Among frequently used experimental antagonists, the selectivity of ICI 118,551 for β 2 -adrenoceptors relative to β 3 -adrenoceptors is comparable to that relative to β 1 -adrenoceptors (Table 2) (Baker 2005;Hoffmann et al 2004).…”
Section: Cell Linesmentioning
confidence: 68%
See 4 more Smart Citations
“…For example, the prototypical antagonist propranolol was reported to have K i values at β 1 -, β 2 ,-and β 3 -adrenoceptors of 1.8, 0.8, and 186 nM, respectively (Table 2). Similarly, much lower β 3 -than β 1 -and β 2 -adrenoceptor affinity was also reported for the clinically used drugs sotalol, alprenolol, carvedilol, metoprolol, atenolol, and bisoprolol in most studies (Baker 2005;Hoffmann et al 2004), although one study reported high β 3 -adrenoceptor affinity of carvedilol (Candelore et al 1999). Among frequently used experimental antagonists, the selectivity of ICI 118,551 for β 2 -adrenoceptors relative to β 3 -adrenoceptors is comparable to that relative to β 1 -adrenoceptors (Table 2) (Baker 2005;Hoffmann et al 2004).…”
Section: Cell Linesmentioning
confidence: 68%
“…Similarly, much lower β 3 -than β 1 -and β 2 -adrenoceptor affinity was also reported for the clinically used drugs sotalol, alprenolol, carvedilol, metoprolol, atenolol, and bisoprolol in most studies (Baker 2005;Hoffmann et al 2004), although one study reported high β 3 -adrenoceptor affinity of carvedilol (Candelore et al 1999). Among frequently used experimental antagonists, the selectivity of ICI 118,551 for β 2 -adrenoceptors relative to β 3 -adrenoceptors is comparable to that relative to β 1 -adrenoceptors (Table 2) (Baker 2005;Hoffmann et al 2004). Similarly, the selectivity of CGP 20,712A for β 1 -adrenoceptors relative to β 3 -adrenoceptors is comparable to that relative to β 2 -adrenoceptors (Table 2) (Baker 2005;Hoffmann et al 2004).…”
Section: Cell Linesmentioning
confidence: 68%
See 3 more Smart Citations